Top twenty risks in software projects: A content analysis and Delphi study - Sonchan,P. (2015)
Risk management is an essential process in software project management. Risk identification and analysis are critical parts of risk management. However, both processes require extensive experience and knowledge to be efficiently performed. Several literatures suggest using checklists which can be used to aid risk identification. However, there is very little information which can guide the risk analysis. This paper extracts and classifies top risks from thirty most frequently cited and recently published literatures on software project risks. A further Delphi study also proposes potential impacts and probabilities of these risks. The results of this paper can be used as a guideline in risk identification and analysis processes on standard software development scenarios. © 2014 IEEE.